2020
DOI: 10.1002/mus.27130
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of theCOVID‐19 pandemic among patients with myasthenia gravis

Abstract: Background Patients with myasthenia gravis (MG) may be particularly vulnerable during the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic due to risk of worsening disease during infection, potential adverse impacts of coronavirus disease 2019 (COVID‐19) treatments on neuromuscular transmission, and a limited ability to fight off infection related to immunosuppressive treatments. Our goal is to understand how patients are experiencing the COVID‐19 pandemic, including where they receive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 28 publications
2
20
0
2
Order By: Relevance
“…Our data suggest that IST is not per se associated with a higher risk of SARS-CoV-2 infection. This might be due to MG patients with IST being more concerned about COVID-19 than MG patients without IST leading to better compliance with hygiene recommendations in Germany during the study period (e.g., lockdowns, social distancing rules) [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that IST is not per se associated with a higher risk of SARS-CoV-2 infection. This might be due to MG patients with IST being more concerned about COVID-19 than MG patients without IST leading to better compliance with hygiene recommendations in Germany during the study period (e.g., lockdowns, social distancing rules) [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an Italian study showed that physical activity in patients with NMD, was significantly reduced during lockdown [ 17 ] which may have negative health consequences as physical activity and exercises are recommended to reduce progression of muscle weakness [ 18 ]. There are also indications of negative emotional consequences of the pandemic and the associated restrictions from studies of the general public [ 19 ] and a few studies in patients with NMD, primarily ALS, such as concerns about COVID-19 infection, loneliness, anxiety and depression [ 12 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that healthcare services should build on the experience gained during the early waves of the pandemic to meet the needs expressed by the neurological patient community [ 11 , 12 , 13 ]. In particular, video appointments and regular phone calls could be added to face‐to‐face consultations to increase contacts with healthcare teams while minimizing virus exposure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%